2022
DOI: 10.1111/bjet.13183
|View full text |Cite
|
Sign up to set email alerts
|

Promoting maker‐centred instruction through virtual professional development activities for K‐12 teachers in low‐income rural areas

Abstract: With an increased interest in makerspace in K‐12 education, professional development (PD) is needed to equip teachers with the knowledge, skills and dispositions to effectively incorporate makerspace and maker technology in teaching. This study examined a virtual PD programme to improve K‐12 teachers' knowledge, attitudes and beliefs in teaching with maker technology. Data were collected from 43 in‐service schoolteachers through project artefacts, survey questionnaires and reflection journals. Results of the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…Participants having a virtual fieldtrip to makerspace with telepresence robots. Reproduced with permission from Chen and Cao (2022)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants having a virtual fieldtrip to makerspace with telepresence robots. Reproduced with permission from Chen and Cao (2022)…”
Section: Methodsmentioning
confidence: 99%
“…Participants having a virtual fieldtrip to makerspace with telepresence robots. Reproduced with permission from Chen and Cao (2022) a good sense of how I appeared to others. "), social presence (eg, "I felt like I was with those who were physically present in my class.…”
Section: Instrumentmentioning
confidence: 99%
“…A pesar de la abundante literatura científica internacional disponible sobre sus potencialidades en el desarrollo profesional docente desde distintas disciplinas curriculares, prácticas de aula (Anderson y Kyzar, 2022;Kartal y Çınar, 2022;Sun et al, 2022;Tan y Chen, 2022) y espacios de enseñanza-aprendizaje (Assis y Vieira-Santos, 2021;Ortega-Sánchez y Gómez-Trigueros, 2020), continúa siendo necesario evaluar sus efectos en el ámbito de la formación inicial del profesorado (Aktaş y Özmen, 2020; Ismaeel y Aktas, 2022;Widyasari et al, 2022). En esta línea, ha sido demostrada su utilidad e impacto en el desarrollo profesional del profesorado en activo, a través de la mejora del conocimiento, autoeficacia, competencia digital y habilidades para la integración de tecnología en el aula (Chen y Cao, 2022;Oda et al, 2020).…”
Section: Figura 1 Modelo Tpackunclassified
“…Various studies (Aslan & Zhu, 2017;Heredia & Fisher, 2022;Lachner et al, 2021;Yeni & Gecu-Parmaksiz, 2016) found that undergraduate programs need to support and encourage the development of pre-service teachers in technology integration skills and knowledge to use instructional technologies or maker tools in their future teaching environments more effectively. Similarly, PD programs play a significant role in providing in-service teachers with ongoing support for contributing to their pedagogical and tech skills (Chen & Cao, 2022;Dogan et al, 2021;Hughes & Morrison, 2022;Stevenson et al, 2019). Teachers found PD sessions beneficial when using their new understanding and experience to impact their students' learning (Martin et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…PD programs effectively support educators' needs, learning new strategies for making interdisciplinary connections in the curriculum or new pedagogies (Chen & Cao, 2022;Dogan et al, 2021;Hughes & Morrison, 2022;Stevenson et al, 2019) and providing new physical and online tech tools for implementing them into the teaching environment (Lawless & Pellegrino, 2007;Wilkerson et al, 2016). During a six-week maker-focused PD program, this paper provides an overview of teachers' user experiences of innovative technologies to understand their experiences and challenges using these tools online.…”
Section: Introductionmentioning
confidence: 99%